Numerical modelling of boom and oil spill with SPH - Violeau, D.; Buvat, C.; Abed-Meraim, K.; de Nanteuil, E. (Coastal engineering (Amsterdam), 2007)
The protection of coastal areas against oil pollution is often addressed with the use of floating booms. These bodies are subject to an empirical design always based on physical models. Indeed, the numerical modelling of a two-phase flow (oil and water) with complicated free surface in the vicinity of a floating body is a challenging issue. The Smoothed Particle Hydrodynamics (SPH) Lagrangian numerical method is appropriate to such simulations since it allows the modelling of complex motions and fluid–structure interactions. In this paper we first study the mechanism of oil leakage by entrainment due to combined turbulent production and buoyancy. Then, we present the main features of the SPH method in a turbulent formalism and apply this model to predict the motion of a boom and an oil spill in an open-channel and a wave flume, for three types of oil (heavy, light and emulsion). Numerical results are compared to experiments and used to depict criteria for oil leakage. It appears that oil leakage by entrainment occurs when the surface water velocity upstream the boom exceeds a critical value which was estimated around 0.5 m/s for a light oil under steady current. A more accurate criterion is derived from theoretical considerations and successfully compared to numerical experiments. In the case of wave flume, no validation from experiments could be made. However, it appears that leakage occurs from a critical wave height between 0.5 and 1.0 m, for the tested wave period of 4 s. A more extended panel of numerical tests would allow a better knowledge of the involved mechanisms and critical parameters. An extensive use of this model should extend our knowledge regarding the mechanisms of oil leakage under a boom and allow a better and easier design of booms in the near future.